Mother Awareness Regarding Oral Contraceptive Pills in Family Planning Center in Kirkuk City - Elham Saeed Shaker; Salwa Hazim Al Mukhtar (College of Nursing,University of Mosul, 2015)
Background and aim: The family planning involves choosing if and when to have children. It includes contraception, the prevention of pregnancy as well as methods to achieve pregnancy this method used by couples having difficulty attaining pregnancy. In addition, using contraceptives has been shown to promote a woman's sense of autonomy and increase her ability to make decisions in other areas of her life This study aims at identifying mother's awareness regarding to oral contraceptive pills in Kirkuk city, as well as to find a relationship between women's knowledge and attitude with some socio- demographic characteristics such as (mother's age, level of education, occupation, number of children, socioeconomic status, medical data, miscarriage and parity). Materials and method: A descriptive study Probability (Purposive sample) consists of 500 women who attended the typical primary health care centers in Kirkuk city, for a period from November, 1st , 2013 to October, 1st, 2014. Constructed questionnaire designed to questioned women's about oral contraceptive pills, The data were collected through the use of the interview. They were analyzed through the application of descriptive statistical analysis (frequency and percentage) and inferential statistical data analysis (ANOVA). Results: The findings of the study indicated that (37%) were in the age group (35 and above), and (37.7%) of the sample were graduating from primary school, (78.2%) of them were a housewife, (59.2%) of the sample had barely sufficient monthly income. The study indicated that (41%) have (1-3) children, and (59.6%) had no history of chronic disease. Conclusion: Further studies include samples from rural areas and compare their awareness to the urban women regarding family planning methods. Recommendations: the study found a high awareness regarding to oral contraceptive pills among women. In addition, a significant relationship was found between level of education, number of children and awareness regarding to oral contraceptive pills. Keywords: Awareness, Contraceptive pills Ectopic pregnancy, Family Planning, Mini pill, miscarriage.